MUSIC COLLAB: An IoT and ML Based Solution for Remote Music Collaboration (Student Abstract) - Nayar, Nishtha; Lohani, Divya (Proceedings of the AAAI Conference on Artificial Intelligence, 2020)
Communication using mediums like video and audio is essential for a lot of professions. In this paper, interaction with real-time audio transmission is looked upon using the tools in the domains of IoT and machine learning. Two transport layer protocols - TCP and UDP are examined for audio transmission quality. Further, different RNN models are examined for their efficiency in predicting music and being used as a substitute in case of loss of packets during transmission.